2014
DOI: 10.1590/0004-282x20140133
|View full text |Cite
|
Sign up to set email alerts
|

Lower trait frontal theta activity in mindfulness meditators

Abstract: Acute and long-term effects of mindfulness meditation on theta-band activity are not clear. The aim of this study was to investigate frontal theta differences between long- and short-term mindfulness practitioners before, during, and after mindfulness meditation. Twenty participants were recruited, of which 10 were experienced Buddhist meditators. Despite an acute increase in the theta activity during meditation in both the groups, the meditators showed lower trait frontal theta activity. Therefore, we suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…Thus, we suggest that the meditative state of “mindfulness” technique proposed by Buddhist meditation studied is more related to the development of a “brain more general integrative mechanism” rather than a specific mechanism of integrative focused attention and memory processes [ 15 , 32 ], since the theta/beta induced ratio power (absolute values), the relative theta power, and theta/beta relative ratio power (also in its induced component) were significantly correlated with the FWMP; as if assiduous practitioner had allowed himself, deliberately, innumerable “distractions” during practice; allowing thoughts, feelings, or sensations arise without sticking to any of them [ 33 ]; corroborating the interpretation of “right mindfulness” as the seventh via the “Noble Path” of Buddhism that means “being aware of what is occurring at the present time watching all the thoughts and feelings as they sungem without clinging to them” opposing the focused attention called “right concentration” defined as the ability to focus, “the mind's ability to stand firm on an object” [ 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that the meditative state of “mindfulness” technique proposed by Buddhist meditation studied is more related to the development of a “brain more general integrative mechanism” rather than a specific mechanism of integrative focused attention and memory processes [ 15 , 32 ], since the theta/beta induced ratio power (absolute values), the relative theta power, and theta/beta relative ratio power (also in its induced component) were significantly correlated with the FWMP; as if assiduous practitioner had allowed himself, deliberately, innumerable “distractions” during practice; allowing thoughts, feelings, or sensations arise without sticking to any of them [ 33 ]; corroborating the interpretation of “right mindfulness” as the seventh via the “Noble Path” of Buddhism that means “being aware of what is occurring at the present time watching all the thoughts and feelings as they sungem without clinging to them” opposing the focused attention called “right concentration” defined as the ability to focus, “the mind's ability to stand firm on an object” [ 34 – 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, only a handful of studies have reported an attenuation of theta activity. For example, Tanaka et al (2014) found during rest periods that long-term, relative to shortterm, mindfulness practitioners had lower levels of theta activity. This attenuated theta activity in mindfulness experts may reflect the expert practitioner's ability to limit the processing of unnecessary information to facilitate awareness and acceptance of the context in which they exist, akin to a bottom-up regulatory process (Chiesa et al, 2013).…”
Section: Thetamentioning
confidence: 99%
“…(1996a) reported that fronto‐parietal theta rhythms were elicited by emotional thoughts. In addition, frontal theta decrease when disruptive thoughts are reduced (Tanaka, Peressutti, Teixeira, Cagy, Piedade & Nardi, 2014), supporting that theta is affected by or affect intrusive imagery‐related thoughts. This, together with our findings of theta being linked to electrodermal activity and modulated by attachment, suggest that frontal theta power during negative imagery when holding hands mainly reflects emotional rather than cognitive processes.…”
Section: Discussionmentioning
confidence: 99%